Enhancing industrial competency: Bulldozer operation training as a strategy for youth empowerment in Rantih Village, Sawahlunto - Nasution, Ichsan; Febriansyah, Ilham; Wisesa, Budi Utomo; Zulfadli, Zulfadli; Yuliady, Ilham; Rahmadani, Rahmadani; Firmansyah, M. Sadly (Community Empowerment, 2026)
This community service activity aims to improve the technical skills of young people in Rantih Village, Talawi District, Sawahlunto City in operating bulldozer heavy equipment. The main problem in this village is the high unemployment rate due to low technical skills and limited access to job training that meets industry needs. The training program was carried out through a one-day theoretical and practical field learning method involving 10 participants. The activity was facilitated by lecturers and industry practitioners who are certified heavy equipment operators. The training results showed a significant improvement in the participants' knowledge and skills, particularly in the areas of basic operation, equipment maintenance, and work safety implementation, by 82%. Additionally, this activity successfully built a partnership network between universities, village governments, and the industrial world. This program is expected to continue on an ongoing basis as a form of youth empowerment towards economic independence.